2012
DOI: 10.5001/omj.2012.81
|View full text |Cite
|
Sign up to set email alerts
|

Is Previous Tubal Ligation a Risk Factor for Hysterectomy because of Abnormal Uterine Bleeding?

Abstract: The result of this study showed that previous tubal sterilization is not a risk factor for undergoing hysterectomy because of abnormal uterine bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…10 In present study, 77 (38.5%) women had undergone tubal ligation as a method of sterilization who had the complaint of AUB. Similar results (44%) were found in a study conducted by Sanam et al 13 Letchworth et al said in his study that about 20% of women will experience heavier menses after TL. 14 This was probably because TL technique sometimes disturbed the ovarian blood supply leading to congestion which led to disturbance in ovarian function.…”
Section: Discussionsupporting
confidence: 87%
“…10 In present study, 77 (38.5%) women had undergone tubal ligation as a method of sterilization who had the complaint of AUB. Similar results (44%) were found in a study conducted by Sanam et al 13 Letchworth et al said in his study that about 20% of women will experience heavier menses after TL. 14 This was probably because TL technique sometimes disturbed the ovarian blood supply leading to congestion which led to disturbance in ovarian function.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, sterilization appears to be related to an increased risk of hysterectomy. Biologically, tubal ligation has been associated with higher risk of menstrual disorders and gynaecological ailments in some research conducted in the United States, although evidence is mixed ( Hillis et al 1998 ; Olenick 1998 ; Ozerkan et al 2010 ; Moradan and Gorbani 2012 ; Nankali et al 2012 ). Widespread, normalized surgical sterilization in India may in fact be a precedent for the normalization of ‘permanent’ solutions to reproductive ailments, for both women and providers.…”
Section: Discussionmentioning
confidence: 99%
“…They had retrospectively analyzed medical records of 67 patients who had a hysterectomy for abnormal uterine bleeding. 17 They found that there was no significant difference in hysterectomy between those who were tubectomised (28.36%) and those who were not tubectomised (71.64%). But in our study 90.09% of the patients were tubectomised.…”
Section: Discussionmentioning
confidence: 99%